Proteome selectivity profiling of photoaffinity probes derived from imidazopyrazine-kinase inhibitors - Dimitris Korovesis; Christel Mérillat; Rita Derua; Steven H. L. Verhelst (Communications Chemistry)
Abstract Kinases are attractive drug targets, but the design of highly selective kinase inhibitors remains challenging. Selectivity may be evaluated against a panel of kinases, or – preferred – in a complex proteome. Probes that allow photoaffinity-labeling of their targets can facilitate this process. Here, we report photoaffinity probes based on the imidazopyrazine scaffold, which is found in several kinase inhibitors and drugs or drug candidates. By chemical proteomics experiments, we find a range of off-targets, which vary between the different probes. In silico analysis suggests that differences between probes may be related to the size, spatial arrangement and rigidity of the imidazopyrazine and its substituent at the 1-position.